2013
DOI: 10.12720/joams.1.1.124-128
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Development of a Web-Based Virtual Closet: The Smart Closet Project

Abstract: Smart Closet is a web-based recommendation system where users can register and create their own virtual closet .In the Smart Closet system; users can add items, search, and find matches for items from the personal collection of clothing within the internal database. Moreover, users can search for matches of their clothing items from virtual vendors collections that exist in the database .The system can also make recommendations based on the user's pre-specified preferences, sex, item type, seasonal fabrics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…They surveyed 46 women and found that 37% of these women had one to ten clothing items that they could not wear because they did not fit, 17% had 11 to 20, and 15% had 21 to 50 unwearable items. They even felt difficulty in coordinating their clothes within a limited time in the morning [5] and in selecting the right or key items of clothing for the right occasion from a large personal collection [6,7]. These findings show that consumers are overwhelmed by clothes in their disorganized wardrobes, and it leads to unnecessary and impulse consumption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They surveyed 46 women and found that 37% of these women had one to ten clothing items that they could not wear because they did not fit, 17% had 11 to 20, and 15% had 21 to 50 unwearable items. They even felt difficulty in coordinating their clothes within a limited time in the morning [5] and in selecting the right or key items of clothing for the right occasion from a large personal collection [6,7]. These findings show that consumers are overwhelmed by clothes in their disorganized wardrobes, and it leads to unnecessary and impulse consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Technology, such as that of virtual wardrobes, can suggest solutions to consumers on how they can organize their wardrobes and reduce their overconsumption. A virtual wardrobe is a service based on the web that enables users to create and manage their personal wardrobes digitally [7]. This is also known as a smart closet/wardrobe [6][7][8][9], intelligent wardrobe [10], or e-wardrobe [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology, such as virtual wardrobes, can suggest options and may reduce consumption. A virtual wardrobe is a web-based service that allows users to register and create wardrobes by searching, organizing, and adding clothing from a digitized personal collection of clothing that are available from their actual physical closets (Al-Omar et al, 2013). It recommends outfits based on factors such as the weather, season, colors, styles, events, and user emotions.…”
Section: Introductionmentioning
confidence: 99%
“…However, selecting and matching clothes from a cluttered closet is still a hard task for consumers, as the notion says "a closet full of clothes but nothing to wear" (Roshitsh, 2019). Tackling these problems, Smart Closet has emerged in recent years as an electronic wardrobe assistant, providing functions including virtual wardrobe management, intelligent outfit coordination, and personalized shopping guide (Al-Omar et al, 2013). Additionally, users are able to share their coordinated outfits and get inspiration from others in the Smart Closet community.…”
mentioning
confidence: 99%